Automatic determination of heart rates from microscopy videos of early life stages of fish. Issue 16 (17th September 2017) - Nepstad, Raymond; Davies, Emlyn; Altin, Dag; Nordtug, Trond; Hansen, Bjørn Henrik
ABSTRACT: Toxic effects of organic hydrophobic contaminants include impacts on fish heart rate (HR) and cardiac functioning. Thus, in ecotoxicology as well as aquaculture and even medicine, fish heart functioning plays an important role in application areas. The aim of this study was to assemble a pipeline of image processing and statistical techniques to extract HR information from microscopy videos of the embryo and larval stages of three species of fish (Atlantic cod, haddock, and Atlantic bluefin tuna). The method enables automatic processing for a large number of individuals, saving a significant amount of time compared with manual processing, while simultaneously eliminating the type of errors such a manual process might incur.